Anterior Urethral Advancement as a Single-Stage Technique for Repair of Anterior Hypospadias: Our Experience - Gite, Venkat A.; Nikose, Jayant V.; Bote, Sachin M.; Patil, Saurabh R. (Urology Journal, 2017)
Purpose: Many techniques have been described to correct anterior hypospadias with variable results. Anterior urethral advancement as one stage technique was first described by Ti Chang Shing in 1984. It was also used for the repair of strictures and urethrocutaneous fistulae involving distal urethra. We report our experience of using this technique with some modification for the repair of anterior hypospadias. Materials and Methods: In the period between 2013-2015, 20 cases with anterior hypospadias including 2 cases of glanular, 3 cases of coronal, 12 cases of subcoronal and 3 cases of distal penile hypospadias were treated with anterior urethral advancement technique. Patients' age groups ranged from 18 months to 10 years. Postoperatively, patients were passing urine from tip of neomeatus with satisfactory stream during follow up period of 6 months to 2 years. Results: There were no major complications in any of our patients except in one patient who developed meatal stenosis which was treated by periodic dilatation. Three fold urethral mobilization was sufficient in all cases. Conclusion: Anterior urethral advancement technique is a single-stage procedure with good cosmetic results and least complications for anterior hypospadias repair in properly selected cases.